2007
DOI: 10.1002/bit.21458
|View full text |Cite
|
Sign up to set email alerts
|

Free nitrous acid inhibition on anoxic phosphorus uptake and denitrification by poly‐phosphate accumulating organisms

Abstract: Nitrite has been found in previous research an inhibitor on anoxic phosphorus uptake in enhanced biological phosphorus removal systems (EBPR). However, the inhibiting nitrite concentration reported varied in a large range. This study investigates the nitrite inhibition on anoxic phosphorus uptake by using four different mixed cultures performing EBPR with pH considered an important factor. The results showed that the protonated species of nitrite, HNO(2) (or free nitrous acid, FNA), rather than nitrite, is lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 36 publications
4
79
3
Order By: Relevance
“…Pijuan et al 5 showed that the aerobic phosphorus uptake was inhibited by 50% when FNA reached 0.52 3 10 23 mg HNO 2 -N/L. Anoxic phosphorus uptake was also significantly affected by FNA presence 14 , and 0.02 mg HNO 2 -N/L would cause the complete loss of anoxic phosphorus uptake 11 . Furthermore, anaerobic metabolisms of PAOs were also severely affected by FNA, and Ye et al 8 demonstrated that FNA had an adverse effect on carbon source uptake even at 1.0 3 10 23 mg HNO 2 -N/L.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pijuan et al 5 showed that the aerobic phosphorus uptake was inhibited by 50% when FNA reached 0.52 3 10 23 mg HNO 2 -N/L. Anoxic phosphorus uptake was also significantly affected by FNA presence 14 , and 0.02 mg HNO 2 -N/L would cause the complete loss of anoxic phosphorus uptake 11 . Furthermore, anaerobic metabolisms of PAOs were also severely affected by FNA, and Ye et al 8 demonstrated that FNA had an adverse effect on carbon source uptake even at 1.0 3 10 23 mg HNO 2 -N/L.…”
mentioning
confidence: 99%
“…Especially in some WWTPs that achieve nitrogen removal via the nitrite pathway, the accumulated concentration could reach up to 40 mg/L 10 . Previous researchers considered that the intermediate of nitrification and denitrification (i.e., nitrite) caused seriously inhibition on the metabolisms of PAOs, but recently there have been increasing evidences showing that FNA, the protonated form of nitrite, rather than nitrite is the actual inhibitor 5,11,12 . For example, it was reported that FNA could inhibit aerobic phosphorus uptake seriously at a low level of 0.5 3 10 23 mg HNO 2 -N/L 11 , and more than 1.5 3 10 23 mg HNO 2 -N/L could result in the complete loss of aerobic phosphorus uptake 13 .…”
mentioning
confidence: 99%
“…The cells then need more energy to maintain the proton balance and consequently less energy is available for metabolism and growth (Rottenberg, 1990). Studies of enrichments of the PAO Accumulibacter show that during exposure to higher FNA concentrations the cellular ATP levels are more rapidly consumed (Zhou et al, 2007, Zhou et al, 2010. The rapid depletion of intracellular ATP is presumed to be responsible for cell lysis (Schimz, 1980).…”
Section: Mechanisms Of Fna-induced Inhibitory and Biocidal Effects Ofmentioning
confidence: 99%
“…Zhou et al (2007) found that nitrite, at a concentration ranging from 35.9 to 103.5 mg N/L, was able to inhibit the anoxic phosphorus (P) uptake in enhanced biological phosphorus removal (EBPR)…”
Section: Nitrite Application In Wastewater Industrymentioning
confidence: 99%